Disaster Risk Management Programs for Priority Countries - Global Facility for Disaster Reduction and Recovery (World Bank, Washington, DC, 2015)
In GFDRR ’s track two, mainstreaming disaster risk reduction in development, this lead to a prioritization of operations in 20 core countries, including Burkina Faso, Djibouti, Ethiopia, Ghana, Haiti, Indonesia, Kyrgyz Republic, Madagascar, Malawi, Mali, Marshall Islands, Mozambique, Nepal, Panama, Papua New Guinea, Senegal, Solomon Islands, Togo, Vietnam, and Republic of Yemen. The countries were selected due to their high vulnerability to natural hazards and low economic resilience to cope with disaster impacts including anticipated climate change and variability. Two thirds of the countries are least developed countries and twelve are highly indebted poor countries. Nine are from Africa and several others are Small Island States at high risk. These 20 core countries will receive 80 percent of available funds while 20 percent will be made available for flexible, innovative, high impact grants, such as those that catalyze increased investment programs and integration of disaster risk reduction and climate change adaptation in development in any disaster prone country. A multi-stakeholder planning process lays the foundation for the comprehensive national programs for disaster risk reduction and climate change adaptation. The process ensures the facilitation of ownership by governments for their risk. The presented programs are indicative and further dialogue with the Governments and other partners will refine the agendas as the detailed planning and implementation phases start. At the sixth meeting of the GFDRR Consultative Group in Geneva, disaster risk management plans are put forward for 25 out of the 31 priority and donor-earmarked countries. The plans for the six remaining countries of Burkina Faso, Madagascar, Malawi, Mali, Senegal, and Timor-Leste will be submitted at the seventh meeting of the GFDRR Consultative Group since consultations in these countries are still ongoing.